Facharztweiterbildung quo vadis? - Krusche, M.; Sewerin, P.; Kleyer, Arnd; Mucke, J.; Vossen, D.; Morf, H. (Zeitschrift für Rheumatologie, 2019)
Background: In May 2018 a revision of the training regulations for German doctors (MWBO) was passed which will significantly impact the medical training for German rheumatologists. The goal of this paper was to create an overview of the status quo in advanced medical training in this field. Methods: A quantitative and qualitative analysis was conducted to identify the strengths and weaknesses of the current continuous education in the field of rheumatology in Germany. The number of newly trained specialists in rheumatology in the years 2015 to 2017 was determined from the regional medical associations. Furthermore, an online survey assessing the training conditions of assistant physicians was conducted. 71 physicians participated in the nationwide survey. Results: In 2015 (53 specialists), in 2016 (43 specialists) and in 2017 (43 specialists) completed their training in the field of rheumatology. The online survey of assistant physicians found that the medical training was graded 3.1 on a scale of 1 to 6 (SD ± 1.1). 19.4% of respondents reported that they had regular mentoring, and 41.7% had on-the-job evaluations. Deficits were evident concerning practical diagnostic skills: 22.8% of the physicians were not practicing joint ultrasonography and another 20% performed it only once a month. As points of criticism 46.6% mentioned a missing structure in training programme and 33.3% noted a lack of supervision. The majority of respondents wanted more training options, supervision and better practical training in ultrasound diagnostics. Conclusion: The nationwide number of newly acquired specialist qualifications (between 2015 and 2017) showed a decreasing trend. It is to be feared that the numbers will continue to stagnate, which increases the importance to invest further in medical education. The online survey also showed that the current medical training in Germany has deficits. Here, the new MWBO could create better guidelines for a structured training, which should be guided by the principle of “Teach to Target”.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Advanced training; Investigation techniques; Model continuing training regulations; Specialist numbers; Teach to target